Dormancy-like Phenotype of Aggregatibacter actinomycetemcomitans: Survival during Famine - Natalia O. Tjokro; Carolyn B. Marks; Ashley Wu; Casey Chen (Pathogens, 2024)
Microbes frequently experience nutrient deprivations in the natural environment and may enter dormancy. Aggregatibacter actinomycetemcomitans is known to establish long-term infections in humans. This study examined the dormancy-like phenotype of an A. actinomycetemcomitans strain D7S-1 and its isogenic smooth-colony mutant D7SS. A tissue culture medium RPMI-1640 was nutrient-deficient (ND) and unable to support A. actinomycetemcomitans growth. RPMI-1640 amended with bases was nutrient-limited (NL) and supported limited growth of A. actinomycetemcomitans less than the nutrient-enriched (NE) laboratory medium did. Strain D7S-1, after an initial 2-log reduction in viability, maintained viability from day 4 to day 15 in the NL medium. Strain D7SS, after 1-log reduction in viability, maintained viability from day 3 to day 5. In contrast, bacteria in the NE medium were either non-recoverable (D7S-1; >6-log reduction) or continued to lose viability (D7SS; 3-log reduction) on day 5 and beyond. Scanning and transmission electron microscopy showed that A. actinomycetemcomitans in the NL medium formed robust biofilms similar to those in the NE medium but with evidence of stress. A. actinomycetemcomitans in the ND medium revealed scant biofilms and extensive cellular damage. We concluded that A. actinomycetemcomitans grown in the NL medium exhibited a dormancy-like phenotype characterized by minimum growth, prolonged viability, and distinct cellular morphology.